(untitled) (Journal of the College of Basic Education, 2022)
Let R be a commutative ring with unity and let M be a unitary R-module. The goal of this work is to investigate the relationships between weakly Quasi-prime modules and coprime modules(dual notion of prime modules) .Also we give some basic properties of the two concepts